Current status of plant pathogens of agricultural importance for Colombia. A review - Amaro, Tiago Miguel Marques Monteiro; Cope, Jonathan; Franco-Orozco, Bárbara (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2021)
Plant disease still plays a major role in limiting agricultural production worldwide. Pathogens and pests reduce crop yield and can cause large reductions in crop quality. Colombia is no exception as it contends with many devastating pathogens that present a major threat to the country’s agricultural sector. This review is important because it highlights four of the more damaging pathogens that affect the economics of important crops in Colombia - Xanthomonas phaseoli pv. manihotis (Xpm), Fusarium oxysporum f. sp. cubense (Foc), Phytophthora palmivora, and Hemileia vastatrix. This paper was based on an extensive literature search for plant diseases in Colombia in databases such as PubMed and Google Scholar. Moreover, this search was complemented with research on crop production in the country in databases made available by the Food and Agriculture Organization of the United Nations (FAO). The four pathogens reviewed in this paper were chosen not only because of their current devastating effects on Colombia’s agricultural production but also because of their potential to cause further damage in the near future. Understanding the current situation of these crop pathogens in Colombia is imperative for state directives aimed at developing informed and efficient control strategies.